2020
DOI: 10.1039/c9nr08570j
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the protein corona: coating of black phosphorus nanosheets enables macrophage polarization via calcium influx

Abstract: BPNSs covered with plasma corona could promote the activation and polarization of macrophages and enhance the anticancer ability of macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…[56] The BP-corona complexes could also interact with calmodulin (an ubiquitously expressed Ca 2+ binding protein) to activate stromal interaction molecule 2 and facilitate Ca 2+ influx in macrophages, promoting the polarization of M0 macrophages into M1 phenotype by inducing the activation of p38 and NF-κB pathways. [57] This immune perturbation could promote cancer therapy. Similarly, bare borophene NSs did not provoke immune responses mediated by macrophages, while the protein corona endowed this material with pro-inflammatory and immunoregulatory activity.…”
Section: Xenes Materialsmentioning
confidence: 99%
“…[56] The BP-corona complexes could also interact with calmodulin (an ubiquitously expressed Ca 2+ binding protein) to activate stromal interaction molecule 2 and facilitate Ca 2+ influx in macrophages, promoting the polarization of M0 macrophages into M1 phenotype by inducing the activation of p38 and NF-κB pathways. [57] This immune perturbation could promote cancer therapy. Similarly, bare borophene NSs did not provoke immune responses mediated by macrophages, while the protein corona endowed this material with pro-inflammatory and immunoregulatory activity.…”
Section: Xenes Materialsmentioning
confidence: 99%
“…mRNA levels of M2-related genes IL-10, CD206 and arginase-I were decreased in agreement with M1 polarization. [203] In general, black phosphorus can induce inflammatory effects and leads to pro-M1 macrophage phenotypes, with toxicity remaining cell-type-dependent. (Table 4)…”
Section: Black Phosphorusmentioning
confidence: 99%
“…It has been confirmed that BPcorona complexes interact with stromal interaction molecule 2 (STIM2) inducing Ca 2+ influx, which further induces the activation of p38 and NF-κB and causes the polarization of M0 macrophages to M1 macrophages. 131 The NF-κB pathway Environmental Science: Nano Tutorial review plays an essential role in inflammatory reactions, 132 that is why the levels of proinflammatory cytokines such as IL-1ß, IL-6, IL-8. IL-9 and IL-10 rise significantly.…”
Section: View Article Onlinementioning
confidence: 99%